Electrochemical characteristics and collectorless flotation behavior of galena: With and without the presence of pyrite. (April 2015) - Qin, Wenqing; Wang, Xingjie; Ma, Liyuan; Jiao, Fen; Liu, Ruizeng; Yang, Congren; Gao, Ke
Highlights: Research of sulfide minerals were undertaken on mixed minerals. Oxidation–reduction process of coupled electrode is superimposition of each mineral. Oxidation speed of galena increased with the presence of pyrite. Zeta potential showed significant influence on the generation of surface products. The floatability of galena in artificial mixture is related to the content of pyrite. Abstract: The electrochemical characteristics, surface properties and collectorless flotation behavior of galena with and without the presence of pyrite have been studied. Electrochemical tests confirmed previous reports in the literature that galena is electrochemically more active than pyrite and serves as the anode in galvanic combinations with pyrite. Cyclic voltammograms and polarization curves tests indicated that the addition of pyrite did not change the oxidative and reductive products of galena, but increased the current density during oxidation process. Zeta potential of galena showed a significant difference when coupled with pyrite, due to the influence on the oxidation of the mineral surface. Flotation results showed that the presence of pyrite leading to an influence on the collectorless floatability of galena and the influence correlation with the composition proportion of each mineral.